2023
DOI: 10.1021/acsanm.3c01699
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Plasmonic Responses of Multi-Shaped Au Nanostructures Hybridized with Few-Layer WS2 Nanosheets for Organic Solar Cells

Abstract: Raising the photocurrent and successively achieving a high power conversion efficiency (PCE) in organic solar cells (OSCs) with physically thin photoactive layers is usually a highly challenging task because of their excitonic nature. Herein, we utilized the synergistic plasmonic effects of multi-shaped Au nanostructures (diameter/edge length ∼50 nm) hybridized with few-layer WS 2 nanosheets in improving the photocurrent of fullerene and non-fullerene-based OSCs. A PCE enhancement of more than 15% and an exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“… 101 Furthermore, Abhijith et al explored the synergistic plasmonic effects of multi-shaped Au nanostructures positioned on WS 2 nanosheets to enhance the photocurrent of fullerene- and non-fullerene-based OSCs. 22 Various shapes of Au nanostructures, including spheres, cubes, ellipsoids, rods, prisms, and trapezoids, each with a diameter or edge length of approximately 50 nm, were hybridized with a few layers of WS 2 nanosheets, forming Au–WS 2 nanohybrid structures. The incorporation of Au–WS 2 nanohybrids as an interlayer between PEDOT:PSS and photoactive layers enhanced the light-harvesting capability of OSCs across a broad wavelength range of 350–700 nm, achieving a significant PCE increase of 12.41%.…”
Section: Effect Of Aunp Morphology On Osc Performancementioning
confidence: 99%
See 1 more Smart Citation
“… 101 Furthermore, Abhijith et al explored the synergistic plasmonic effects of multi-shaped Au nanostructures positioned on WS 2 nanosheets to enhance the photocurrent of fullerene- and non-fullerene-based OSCs. 22 Various shapes of Au nanostructures, including spheres, cubes, ellipsoids, rods, prisms, and trapezoids, each with a diameter or edge length of approximately 50 nm, were hybridized with a few layers of WS 2 nanosheets, forming Au–WS 2 nanohybrid structures. The incorporation of Au–WS 2 nanohybrids as an interlayer between PEDOT:PSS and photoactive layers enhanced the light-harvesting capability of OSCs across a broad wavelength range of 350–700 nm, achieving a significant PCE increase of 12.41%.…”
Section: Effect Of Aunp Morphology On Osc Performancementioning
confidence: 99%
“…The utility of achieving multiple plasmonic excitations or tuning the plasmonic activity has been demonstrated through the combination of different shapes of AuNPs. 21–23,33 Mixing shapes, such as spheres with rods, spheres with bipyramids, and hybrid configurations have been reported, leveraging the cooperative effects of distinct plasmonic excitations arising from the combination of AuNP morphologies. 20 Although the incorporation of AuNPs in plasmonic OSCs experienced a decline in popularity, recent publications in 2023, as indicated (Table 1), signify a resurgence of interest.…”
Section: Introductionmentioning
confidence: 99%
“…2,14,15 The current research scenario is focused on addressing these challenges to improve the performance and stability of OSCs. 16−20 With regards to the electron transport layer (ETL) materials, such as conjugated and nonconjugated polymers, 21−23 organic small molecules, 24,25 and transition metal oxides, 26,27 interface engineering for the manipulation of the internal built-in potential using novel molecules and 2D materials 28−30 has exhibited efficient performance in OSCs due to their excellent optical and electronic properties. However, very few reports are available for the hole transport layer (HTL); therefore, a significant finding for HTLs instead of ETLs is still needful.…”
Section: Introductionmentioning
confidence: 99%
“…Solution-processed organic solar cells (OSCs), with their unique features of low weight, flexibility, semitransparency, and inexpensive manufacturing techniques, enable the development of the most promising energy technology for applications such as portable electronics, wearable devices, and building-integrated photovoltaics. The power conversion efficiencies (PCEs) of the state-of-the-art OSCs have been boosted to over 19% in recent years due to the development of novel conjugated wide band gap polymer donors and narrow band gap nonfullerene acceptors (NFAs) for the active layer. In contrast to the outstanding achievements on absorbing layer systems, research on transport layers is far behind. Besides, the long-term sustainability of OSCs remains a challenge. ,, The current research scenario is focused on addressing these challenges to improve the performance and stability of OSCs. With regards to the electron transport layer (ETL) materials, such as conjugated and nonconjugated polymers, organic small molecules, , and transition metal oxides, , interface engineering for the manipulation of the internal built-in potential using novel molecules and 2D materials has exhibited efficient performance in OSCs due to their excellent optical and electronic properties. However, very few reports are available for the hole transport layer (HTL); therefore, a significant finding for HTLs instead of ETLs is still needful .…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the power conversion efficiency (PCE) of organic solar cells (OSCs) has been triggered mainly due to the development of novel wide-bandgap conjugated polymers and low-bandgap non-fullerene acceptors (NFAs), active layer morphology optimization, device interface engineering and utilization of various novel nanomaterials. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Several research groups have reported PCEs of more than 19% in single bulk OSCs. [20][21][22][23][24][25][26] Although high-performance devices have been frequently demonstrated, their PCE and open-circuit voltage (V OC ) still lag behind those of other competing technologies such as Si, GaAs, and perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%